ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFIT DISTRIBUTION MANAGEMENT: Studi Empiris Bank Umum Syariah di Indonesia Periode 2009-2012 - Septyana Bella Kartika; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2014)
This research aims to analyze the factors that influence the Profit Distribution Management on public sharia banks that existed in Indonesia. The dependent variables used in this study is Profit Distribution Management. Independent variables used in this study are Capital Adequacy, Effectiveness of Depositors Funds, Assets Composition, Deposits, Assets Management, Productive and the Rate of Inflation.This research using a sample of sharia banks that listed in Bank Indonesia (BI) in the period 2009-2012. Data were collected using a purposive sampling technique. Analysis of the test used the assumption of classical test, hypothesis test, and multiple regression analysis.Multiple regression analysis test results indicating that the variable Capital Adequacy, Effectiveness of Depositors Funds, Asset Composition, and Productive Assets Management positive effect significantly to Profit Distribution Management. While Deposits and Rate of Inflation have negative effect not significant to Profit Distribution of Management. The results of this study is expected that more sharia banks are capable of performing management of product development for results-based more in line with Islamic Sharia.